Penerapan Hukum International dalam Kasus Pelanggaran Hak Asasi Manusia Berat di Indonesia - Nusantara, Abdul Hakim G. (UI Scholars Hub, 2021)
Since the end of World War II, international law of human rights have a rapid and significant improvement so that it's become the primary source of law when state, international organization, and individual faces the human rights problems in all over the world. Efforts from the world community to improve the system of human rights protection achieve it's culmination point when the UN diplomatic conference agreed the Rome Statuate about International Criminal Court. Indonesia does not ratify that convention because Indonesia already has the law of human rights that is in the Law Number 26 Year 2000. This regulation applied to severlas cases of human rights violation in Indonesia such as Abilio Jose Osorio Soares case, Soedjarwo case, and G.M. Timbul Silaen. In those cases, the definition of